Rozwiązania proekologiczne przy eksploatacji ropy naftowej i gazu ziemnego na złożu Barnówko - Mostno - Buszewo w Polskim Górnictwie Naftowym i Gazownictwie S.A. = Pro-ecological solutions in petroleum (oil) and natural gas mining in the deposits of Barnówko - Mostno - Buszewo in the Polish Oil and Natural Gas Mining - Tatarynowicz, Jan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Paper entitled " Pro-ecological solutions in petroleum (oil) and natural gas mining in the deposits of Barnówko - Mostno - Buszewo fields" deals with one of the major projects undertaken by Polish Oil & Gas Company at the turn of the year 1999. This venture is worth giving special consideration not only because of significant oil and gas production from the home field but also for the reason that environmentally friendly, state-of-the-art engineeringsolutions have been introduced into the exploitation process in these fields.
Keywords: 2 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zagospodarowanie zlewni" (21-22.06.2001)